HUBUNGAN USIA DAN JENIS KELAMIN DENGAN KEJADIAN HIPERTENSI - Mulyati; La Ode Nuh Salam; Suwardha Yunus3; Ricky Z (Stikes Graha Edukasi Makassar, 2023)
Background: Hypertension is a degenerative disease that generally increases slowly with age. Generally, men often experience signs of hypertension in their late twenties, while women after menopause. Objective: This study aims to determine the relationship between age and gender with the incidence of hypertension. Method: This study used a cross-sectional design. Data collection was carried out from 13 to 31 March 2023 using the Accidental Sampling technique. Every respondent who meets the research criteria first has their blood pressure measured using a digital blood pressure monitor, and then is given a questionnaire containing demographic data. Data were analyzed using the Chi-square test with a significance value of 0.05. Results: A total of 60 respondents met the criteria, where it was found that respondents with a high-risk age mostly suffered from hypertension, namely 38 people (63.3%) with a p-value = 0.000, while based on gender, the respondents who suffered from hypertension the most were men. with a total of 27 people (45.0%) with a p-value = 0.002. Conclusion: There is a significant relationship between age and gender and the incidence of hypertension, where in men hypertension usually occurs after the age of 30 years, but in women, it occurs just before menopause. Suggestion: Health service workers are expected to continue providing education to the public regarding hypertension as an effort to increase their knowledge regarding the prevention and treatment of hypertension